Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1002/ange.200907014
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Rhenabenzenes

Abstract: Die ersten sind manchmal die letzten: Während bisher nur stabile Metallabenzole später Übergangsmetalle bekannt waren, wurden nun auch Metallabenzole mit einem frühen Übergangsmetall erhalten: Die luftstabilen Rhenabenzole 1 und 2 (siehe Schema) konnten isoliert und strukturell charakterisiert werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…[8] Since the report of the first isolated metallabenzene in 1982, [9] a variety of stable metallabenzenes have been synthesized in recent years. [7,10] However, research on the functions and applications of these species remains undeveloped. Highly stable and soluble ruthenabenzenes can be obtained from the onepot reaction of RuCl 3 , PPh 3 , and HC CCH(OH)C CH.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Since the report of the first isolated metallabenzene in 1982, [9] a variety of stable metallabenzenes have been synthesized in recent years. [7,10] However, research on the functions and applications of these species remains undeveloped. Highly stable and soluble ruthenabenzenes can be obtained from the onepot reaction of RuCl 3 , PPh 3 , and HC CCH(OH)C CH.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Many interesting chemical properties of metallabenzenes have also been discovered. For example, it has been demonstrated that metallabenzenes can undergo electrophilic substitution reactions, [2a, 5d] cycloaddition reactions, [8d, 9c] nucleophilic addition reactions, [13] and nucleophilic aromatic substitution of hydrogen.…”
mentioning
confidence: 97%
“…The maximum deviation from the least-squares plane through Re1 and C1-C5 is 0.028 for C1. The C1-C2, C2-C3, C3-C4, and C4-C5 bond lengths are 1.310(11), 1.337(11), 1.426 (12), and 1.350 (14) , respectively. The Re-C1 bond length of 1.933 (7) is within the range of those reported for typical Re=CHR(carbene) bonds (1.850-2.143 ), [16,17] and shorter than those reported for typical Re-C(vinyl) bonds (1.996-2.305 ).…”
mentioning
confidence: 99%
“…[1] Previous studies have led to the isolation and characterization of an impressive number of stable metallabenzenes, especially those of osmium, [2][3][4] iridium, [5][6][7][8] platinum, [9] ruthenium, [10,11] and rhenium. [12] Metallabenzynes, [13] which are organometallic compounds derived from formal replacement of a carbon atom or a CÀH group in benzyne with an isolobal transition metal fragment, are closely related to metallabenzenes. At first sight, one might expect that metallabenzynes may be too unstable to be isolated, because organic compounds with a C C bond in the six-membered ring, for example, benzyne and cyclohexyne, are thermally highly unstable because of ring strain.…”
mentioning
confidence: 99%